The Effect of Bottom Passing Practice with Wall and Pairs on the Accuracy of Volleyball - Mahardika, Amanda Reza; Fahmi, Donny Anhar; Hadi, Husnul; Prayogo, Giri (Universitas PGRI Palembang, 2024)
The purpose of this study was to determine which exercises were most effective for improving the accuracy of volleyball underpasses and whether practicing under-passing to the wall and pairing had an effect on that accuracy. volleyball between the practice of Passing Down With the Wall with Pairing with friends. This research method uses experiments with a population of 23 athletes participating in the women's volleyball rosella kalirejo. and a sample of 16 athletes was taken using the purposive sampling technique. The free variable is the bottom passing exercise with the wall, while the bound variable is the training with a partner. Research results: 1) experimental group 1 tcount value = 2.328 > ttable = 1.8125, the practice of lower passing service with a wall had a significant effect. 2) Experimental group 2 tcount value = 6.155 > ttable = 1.8125, training in pairs with friends had a significant effect. The conclusion of The purpose of this study is the accuracy of volleyball passing., practicing with a wall is preferable to practicing in pairs with friends. This research is expected to lead to the application of the bottom passing exercise on the wall to improve the accuracy of volleyball passing